Предмет: Алгебра,
автор: waeshj
sin(-a)-sina*ctg^2(-a)
Ответы
Автор ответа:
0
-sina-sina*ctg^2a = -sina-sina*(cos^2/sin^2)= -sina-(cos^2/sina)=(-sin^2-cos^2)/sina=-1/(sina)
Автор ответа:
0
sin(-a)-sina*ctg^2(-a)=0
-sina+sina*соs^2a/sin^2a= 0
-sina+соs^2a/sina =0
--sin^2a+соs^2a=0
tg^2a=1=0
tga=1 tga=-1
a=П/4+Пк а=-П/4+пк
P.s К-принадлежит к целым числам
Похожие вопросы
Предмет: Қазақ тiлi,
автор: niazalyaaulym
Предмет: Математика,
автор: Poppiesdkkdkdkdk
Предмет: Русский язык,
автор: gusejnlisamil84
Предмет: Алгебра,
автор: Dasha211212